Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Service Excellence pada Restoran di Bawen Kabupaten Semarang - Faizal Ali; Henry Yuliamir (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyse the implementation of Human Resource Management (HRM) in improving service excellence in restaurants in Bawen, Semarang Regency. The problem focuses on how recruitment practices, training, standard operating procedures, performance evaluation, and work culture contribute to improving service quality. To approach this issue, the study employs Human Resource Management theory based on the Resource-Based View and the concept of service excellence in the service industry, which emphasises the strategic role of human resources as a source of competitive advantage. Data were collected through field observations, in-depth interviews with restaurant owners, supervisors, and employees, as well as documentation, and were analysed qualitatively using thematic analysis. The findings show that HRM implementation has been carried out with varying levels of formality, where restaurants with more structured HRM systems tend to deliver more consistent service in terms of friendliness, speed, and accuracy. An important finding of this study reveals a pattern that service excellence is not only determined by formal procedures but also by direct leadership from owners and a strong family-oriented work culture. This study provides a theoretical contribution by strengthening the concept that, in the context of micro and small enterprises, simple yet consistent HRM implementation can serve as a strategic mechanism in building sustainable service excellence.